Experimenting in the Unknown: Lessons from The Manhattan Project. Issue 2 (3rd June 2018) - Gillier, Thomas; Lenfle, Sylvain
Abstract : Experimentation is paramount to innovation. In fact, innovation scholars and practitioners have espoused Thomke's (2003) book titled Experimentation matters: Unlocking the potential of new technologies for innovation . Unfortunately, companies still experience considerable technical and managerial difficulties with organizing experiments under high uncertainty. This study confronts Thomke's experimentation principles with a high uncertainty context by examining experiments conducted by The Manhattan Project from 1943–1945, the initiative that created the first implosion‐type fission bomb. Findings suggest that lack of theoretical knowledge, a crisis of scientific instruments, and absence of pre‐established organizations were critical to such highly uncertain experimentation. We conclude with a discussion of the boundary conditions of Thomke's experimentation principles. Finally, we propose five principles for facilitating the management of experimentation in the unknown.